The physiological basis of wrestling: Implications for conditioning programs - Kraemer, W. J.; Vescovi, J. D.; Dixon, P. (Strength and Conditioning Journal, 2004)
It is possible with proper training to improve the body's buffer system, increase isometric strength, and heighten total body strength and power capabilities in wrestlers within a fatigued environment. The suggestions included in this article provide some general guidelines from which to build a highly integrated wrestling program.